Pedestrian level wind environment investigations in residential complexes in Iraq - Abdulmuttaleb, Khan Ali Hussein (2021)
In urban areas, outdoor thermal comfort influences the performance of people and their work. Wind flow is affected by several parameters, such as the arrangement of buildings and the architecture of buildings with regard to shapes, height of buildings, and aspect ratio of street-canyon width. Modern design techniques will lead to the enhancement of many architectural buildings' thermal performance which may have an impact on Iraq Government’s criteria. While policies and design standards deal with key planning and there are no obvious guidelines in designing buildings that have effective energy performance. Moreover, the contemporary urban design pays no attention to the environmental solution in residential buildings which will lead to the production of a rather large calm zone of wind speed and the potential to increase the risk of pollutant exposure in many areas of outdoor places. Hence, the study aimed to determine the extent of the impacts of wind flow around the outdoor residential buildings at the pedestrian-level wind (PLW) in Iraq and to what extent can they be invested in finding healthy and comfortable living conditions , as well as, focusing to uncover the current practices in outdoor conditions for existing residential buildings in terms of (arrangement, shape, height of the building, and street -canyon width) as well as, the patterns of wind flow behavior among occupants of different models. Consequently, a quantitative field study was conducted to evaluate the wind effects on outdoor spaces in Iraq residential buildings in a hot-dry climate to achieve a comfortable pedestrian thermal level. The field measurement had measured seven points using Digital Anemometer in Al-Salam residential building as a case study in Najaf city in summer (July). Computer simulation (Autodesk CFD) was used to simulate the existing complex building modeling with three wind velocities (1.2, 2.1, and 3.2 m/s) in the winter and summer conditions respectively, based on the meteorological data of Najaf to compare with the simulation results during the summer season obtained from the field measurements under similar conditions and same measured points so that the accuracy of the results could be acquired. In addition, the study investigated the possibility of wind flow on 28 simulation models in Iraq residential buildings based on different parameters such the buildings’ arrangement, shape, height, and aspect ratio of street canyon by using Autodesk CFD simulation with high accuracy mesh and κ-ε turbulence model. The results of Autodesk CFD simulation and field measurements of the existing complex building of Al Salam Residential Complex showed approximately similar data and slight differences in the accurate value with the error percentage of 4.942 %. The modified models with plants are also capable of improving wind flow in Iraq residential buildings through the use of trees with L-shaped arrangement and of different heights. Furthermore, it was observed from the simulation results of the 6 simulation models that the average wind speed in the staggered arrangement at 45° rotation angle is the best distribution which provides the most appropriate average wind speed. Meanwhile, L-shaped buildings with 45° rotation angle is the optimal shape that provides the most appropriate average speed and creates the best outdoor wind environment and the smallest calm zone. In respect of building height, the results confirmed the use of some solutions to make the gradient of the buildings’ height that allows the shortest one to be exposed to the wind first, while the highest to be the last being exposed to the wind, in order to avoid wall impact blockage. With regard to street-canyon width, wind velocity observed in Model 1 and Model 2 for (12 simulations) had accelerated with increasing street width and resulted in high velocity in some areas. The wind flow characteristics have been influenced by the approaching width of the street canyon and the height of building inside the street canyon. The study was also suggested to increase the inter-distance between the blocks or to reduce the height of the blocks so that the aspect ratio (H/W) is 0.5 between the buildings. The results of this study can be used in future design, concerning outdoor voids to provide comfortable thermal in outdoor spaces. In conclusion, the findings of this study contribute towards improving the designing process.